The General Theory as "depression economics"? Financial instability and crises in Keynes's monetary thought - Jörg Bibow (Levy Economics Institute of Bard College, 2020)
This paper revisits Keynes's writings from Indian Currency and Finance (1913) to The General Theory (1936) with a focus on financial instability. The analysis reveals Keynes's astute concerns about the stability/fragility of the banking system, especially under deflationary conditions. Keynes's writings during the Great Depression uncover insights into how the Great Depression may have informed his General Theory. Exploring the connection between the experience of the Great Depression and the theoretical framework Keynes presents in The General Theory, the assumption of a constant money stock featuring in that work is central. The analysis underscores the case that The General Theory is not a special case of the (neo-)classical theory that is relevant only to "depression economics"-refuting the interpretation offered by J. R. Hicks (1937) in his seminal paper "Mr. Keynes and the Classics: A Suggested Interpretation." As a scholar of the Great Depression and Federal Reserve chairman at the time of the modern crisis, Ben Bernanke provides an important intellectual bridge between the historical crisis of the 1930s and the modern crisis of 2007-9. The paper concludes that, while policy practice has changed, the "classical" theory Keynes attacked in 1936 remains hegemonic today. The common (mis-)interpretation of The General Theory as depression economics continues to describe the mainstream's failure to engage in relevant monetary economics.
Keywords: B2; B3; E44; E58; E65; G01; 330; John Maynard Keynes; Great Depression; Financial Crises; Central Banks; Interest Rates; Monetary Theory